Imaging features and percutaneous endoscopic interlaminar decompression of vacuum disc phenomenon-induced lumbosacral radiculopathy: case report - Wu, Longxiao; Meng, Saifei; Li, Peng; Liu, Chunlei (Frontiers in Surgery, 2025)
The vacuum disc phenomenon (VDP), characterized by gas accumulation within degenerated intervertebral discs, is a radiographic hallmark of advanced spinal degeneration. Although this phenomenon is rare, VDP may also rarely present as radiculopathy due to the compression of nerve structures by dynamic gas migration—which is different from typical intervertebral disc protrusion. This phenomenon predominantly affects elderly populations, with computed tomography (CT) imaging serving as the gold standard for detecting hypodense gas pockets and delineating their spatial relationship to nerve roots. Unlike mechanical compression from disc fragments, gas-induced symptoms are uniquely refractory to conservative therapies, necessitating targeted surgical strategies. This report details a 72-year-old female with acute L5 radiculopathy secondary to multilevel VDP, where percutaneous endoscopic interlaminar decompression achieved immediate symptom resolution through precise gas evacuation. The case underscores the critical interplay between imaging interpretation and minimally invasive intervention in addressing this rare yet debilitating complication of spinal degeneration, while advocating for standardized protocols to optimize patient selection and outcomes.